Determination Of Elementary Students’ Learning Styles Reviewed From Gender Aspects - Marleny Leasa; John Rafafy Batlolona; Javier Julian Enriquez; Mehmet Altan Kurnaz (Journal of Education and Learning (EduLearn), 2018)
Students use different styles or ways of receiving and managing information during learning. VARK learning style was developed based on the physiological aspect of students in the form of sensory modalities. This survey research was conducted at 30 elementary schools in Ambon City. The data of student learning was obtained by filling out the learning style questionnaire developed by Fleming. The results showed that 88.7% of students used a learning style (unimodal) and 11.3% of students combined more than one learning style (multimodal). For the unimodal learning styles, kinesthetic is most prevalent in male and female students with a percentage of 58.6%, whereas visuals are least found with a percentage of 6%. The study also revealed that multimodal learning styles were found at all bimodal, trimodal, and quadmodal combinations. The more blend of learning style, hence the frequency of determination of student learning style even less.. The combination of multiple unimodal learning styles with large numbers will result in multimodal learning styles with large numbers.